Acute hematologic, hepatologic, and nephrologic changes after intraperitoneal injections of 18 nm gold nanoparticles in hamsters - Saleh HM (Dove Medical Press, 2016)
Hazem Mohamed Saleh,1 Omar A Soliman,2 Mohamed Osama Elshazly,3 Alaa Raafat,2 Adel K Gohar,2 Taher A Salaheldin41Otolaryngology Unit, Department of Medical Applications, The National Institute of Laser Enhanced Sciences, Cairo University, 2Department of Clinical Pathology, 3Department of Pathology, Faculty of Veterinary Medicine, Cairo University, 4Nanotechnology & Advanced Materials Central Laboratory, Agricultural Research Center, Guiza, EgyptAbstract: In vivo responses to gold nanoparticles (GNPs) vary not only according to the size, shape, surface charge, and capping agent of GNPs but also according to the animal model, the route of administration, and the exposure frequency and duration. We illustrate here the changes in some hematologic parameters, in the hepatic and renal functions, and in the histopathology of solid organs after multiple intraperitoneal injections of 18 nm GNPs in adult male Syrian golden hamsters. We scored the histopathological changes in the liver and kidneys to grade the deleterious effects. Multiple intraperitoneal injections of 18 nm GNPs in hamsters were nonlethal in the short term but resulted in macrocytosis and hypochromasia, leukocytosis, neutrophilia, lymphocytosis, and monocytosis. The hepatic and renal functions showed nonsignificant changes; however, histopathological examination showed hepatic and renal alterations ranging from mild to marked degeneration, with occasional necrosis of hepatocytes and tubular epithelium.Keywords: in vivo, hamsters, nanogold, acute